Post-translational modifications and protein quality control of mitochondrial channels and transporters - Kadam, Ashlesha; Jadiya, Pooja; Tomar, Dhanendra (Frontiers in Cell and Developmental Biology, 2023)
Mitochondria play a critical role in energy metabolism and signal transduction, which is tightly regulated by proteins, metabolites, and ion fluxes. Metabolites and ion homeostasis are mainly mediated by channels and transporters present on mitochondrial membranes. Mitochondria comprise two distinct compartments, the outer mitochondrial membrane (OMM) and the inner mitochondrial membrane (IMM), which have differing permeabilities to ions and metabolites. The OMM is semipermeable due to the presence of non-selective molecular pores, while the IMM is highly selective and impermeable due to the presence of specialized channels and transporters which regulate ion and metabolite fluxes. These channels and transporters are modulated by various post-translational modifications (PTMs), including phosphorylation, oxidative modifications, ions, and metabolites binding, glycosylation, acetylation, and others. Additionally, the mitochondrial protein quality control (MPQC) system plays a crucial role in ensuring efficient molecular flux through the mitochondrial membranes by selectively removing mistargeted or defective proteins. Inefficient functioning of the transporters and channels in mitochondria can disrupt cellular homeostasis, leading to the onset of various pathological conditions. In this review, we provide a comprehensive overview of the current understanding of mitochondrial channels and transporters in terms of their functions, PTMs, and quality control mechanisms.